Assessing urban park equity in Chaoyang District, Beijing using online review data - Ning Zou; Xiayuan Mi; Yang Xiao; Yunyuan Li; Nan Hu (Scientific Reports, 2024)
Abstract Urban parks are essential components of urban ecosystems, providing vital ecological resources for city residents. However, the rapid expansion of high-density urban areas has led to an unequal distribution of park resources, raising growing concerns about spatial equity. To address these challenges, we employed an improved Gaussian two-step floating catchment area (2SFCA) method, considering park quality variations and integrating sentiment scores from park reviews to calculate a comprehensive park accessibility index, accounting for both supply and demand dynamics among park users. The results demonstrate the significance of park management, as users prioritise convenience and cleanliness of public facilities. Recreational quality significantly influences park distribution equity, with areas near Beijing’s initial greenbelt zone showing improved accessibility (IA). Nonetheless, our analysis exposes disparities in urban park resource allocation within the Chaoyang District, indicating relative inequity. Spatial supply and demand mismatches, especially in the northwest and southeast, are evident. To enhance park layout equity, we recommend strategies like identifying and repurposing underused spaces, establishing pocket parks and micro-green areas, and improving recreational facilities. It is crucial to address the needs of vulnerable groups such as older residents and children. These insights stress the importance of ensuring fair urban park access to enhance the well-being of all city residents.